Development of a Talking Stick Learning Model Assisted by Question Boxes on Students' Social Sciences Learning Outcomes - Pongbatu, Julitha; Hasan, Hasan; Misnah, Misnah (PT. Riset Press International, 2024)
Education is business man For build personality in accordance with values in society or as effort help participant educate For develop and improve knowledge, skills, values, attitudes and patterns Act useful behavior​ for life. Formulation problem is there is enhancement results learn social studies students class V against development of the Talking Stick learning model assisted by Question Box, How Smoothness implementation of the Talking Stick learning model assisted by Question Box results learn social studies students class V SDN Kaleroang, Kec. South Bungku, Regency Morowali, What constraint in development of the Talking Stick learning model with the help of Question Box results learn social studies students class V SDN Kaleroang, Kec. South Bungku, Regency Morowali. Research purposes For know constraint in development of the Talking Stick learning model with the help of Question Box results learn social studies students class V SDN Kaleroang, Kec. South Bungku, Regency Morowali. Study This use type study development ( Research and Development). Research and development methods or in Language English Research and Development is method research used​ For produce product certain, and test effectiveness product the. Research result A pre-test was used For know results Study beginning student before given treatment use Development of the Talking Stick learning model assisted by Question Box.